2021
DOI: 10.3389/fonc.2021.689131
|View full text |Cite|
|
Sign up to set email alerts
|

Combinatorial Strategies to Target Molecular and Signaling Pathways to Disarm Cancer Stem Cells

Abstract: Cancer is an urgent public health issue with a very huge number of cases all over the world expected to increase by 2040. Despite improved diagnosis and therapeutic protocols, it remains the main leading cause of death in the world. Cancer stem cells (CSCs) constitute a tumor subpopulation defined by ability to self-renewal and to generate the heterogeneous and differentiated cell lineages that form the tumor bulk. These cells represent a major concern in cancer treatment due to resistance to conventional prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…Consequently, the identification of clinically relevant predictive biomarkers is necessary to individuate specific and effective treatments. On the assumption that a single drug targeting multiple pathways can improve therapeutic efficiency [15][16][17], using the GSCA platform, we extracted the chemicals having a positive and significant correlation with the expression of PCa-and CRPC-gene sets. Globally, our results showed that inhibitors of regulators controlling epigenetic transcription and MAPK signal transduction (Table S11, Figure S6) can represent promising and alternative drugs to counteract PCa progression and resistance acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the identification of clinically relevant predictive biomarkers is necessary to individuate specific and effective treatments. On the assumption that a single drug targeting multiple pathways can improve therapeutic efficiency [15][16][17], using the GSCA platform, we extracted the chemicals having a positive and significant correlation with the expression of PCa-and CRPC-gene sets. Globally, our results showed that inhibitors of regulators controlling epigenetic transcription and MAPK signal transduction (Table S11, Figure S6) can represent promising and alternative drugs to counteract PCa progression and resistance acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…To this extent, we adopted a consensus-based approach for the analysis of multi-source data from reference works and the extraction of a concordant result, identifying two gene sets associated with differential expression patterns between clinically relevant classes: primary vs. metastatic PCa (PCa-gene set) and CRPC AR+ vs. CRPC AR-(CRPC-gene set). A growing body of knowledge highlighted that hitting multiple targets involved in cancer progression improves the therapy effectiveness [15][16][17]. Following this trend, our study aimed to select, among the compounds already in clinical use for other diseases, those targeting the multiple proteins coded by the PCa-and CRPC-gene set to facilitate the development of more effective therapies, especially for advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the development of combinatorial and synthetic lethality strategies targeting UPS represents one of the most challenging approaches to improve anticancer therapeutic efficacy [ 185 , 186 ]. The clinical trials listed in Table 2 demonstrate the higher therapeutic efficacy of dual strategies compared to UPS inhibitors as single agents.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the significant roles of HR in cancer cell survival, monotherapy against HR or in combination with other therapies targeting other biological pathways may efficiently reduce cancer cell survival and induce apoptosis in these cells. 39 The treatment of EC by targeting the regulation of HR and telomerase in EC has interesting results, where telomerase increases HR through the RAD51 pathway and maintains genome stability. Inhibition of telomerase prevents telomere elongation and also increases RAD51.…”
Section: Targeting the Hr Pathway In Cancer Cellsmentioning
confidence: 99%
“…Regarding the significant roles of HR in cancer cell survival, monotherapy against HR or in combination with other therapies targeting other biological pathways may efficiently reduce cancer cell survival and induce apoptosis in these cells. 39 …”
Section: Dna Repair System In Esophageal Cancermentioning
confidence: 99%